2019
DOI: 10.3390/nu11051129
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Dietary Intake in Italy: The Epidemiological “MY FOOD DIARY” Survey

Abstract: Promoting a healthy lifestyle during the first years of life is a key strategy for controlling obesity risk in later life; having good-quality epidemiological data on eating habits of infants and toddlers can improve awareness and possibly the education given by pediatricians to parents and children. With this aim, we performed a survey about the dietary pattern of Italian children in early childhood. We described the intake of energy, macronutrients and fiber, minerals, and vitamins of 443 Italian children (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 27 publications
6
20
2
Order By: Relevance
“…Intake of vitamin D was similar to or higher than that found in other studies [4,12,13,20,22,60], especially when we consider the AMS children. Chouraqui et al [45] indicated that the intake was much higher in children (12-35 months) consuming young-child formula than in those not consuming such products.…”
Section: Vitamin Dsupporting
confidence: 85%
“…Intake of vitamin D was similar to or higher than that found in other studies [4,12,13,20,22,60], especially when we consider the AMS children. Chouraqui et al [45] indicated that the intake was much higher in children (12-35 months) consuming young-child formula than in those not consuming such products.…”
Section: Vitamin Dsupporting
confidence: 85%
“…The use of added salt and sugar intake is inseparably associated with sodium and added/free sugars intake, which also increased with children’s age [ 21 , 22 , 23 , 28 , 37 , 38 , 39 , 40 , 41 ]. Unfortunately, many infants and toddlers around the world have intakes of sodium [ 25 , 26 , 38 , 39 , 42 , 43 ] and added/free sugars [ 22 , 28 , 37 , 39 , 40 , 43 , 44 , 45 ] already close to the upper limit or even above recommendations. Interestingly, many studies conducted on infants and children have shown that boys compared to girls had a higher intake of sodium [ 21 , 23 , 26 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that mainly assessed the intake of sodium, free or added sugars and use of added salt and sugar provide explicit results that the majority of young children may have exceeded sodium and free/added sugars recommendations since the earliest periods when they began eating solids [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. As early introduction of those ingredients is a risk factor of many diet-related non-communicable diseases, which are a public health challenge worldwide [ 29 , 30 ], recognition of the factors associated with the use of salt and sugar is highly important.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the recently published Italian Consensus [35] that recommends the dose of vitamin D in the various age groups is extremely useful, also considering recent dietary surveys which showed insufficient vitamin supplementation during the first years of life [36].…”
Section: Reviewmentioning
confidence: 99%
“…A three-day record about the nutrient’s intake has been composed by parents of 443 Italian children during the first year of life (age 6.4–131 months) [36]. Interestingly, most of children exceeded in the doses of protein intake, simple carbohydrates and saturated fats above the limits of the Italian Dietary Reference Values, with a low intake of fiber and polyunsaturated fats.…”
Section: Reviewmentioning
confidence: 99%